ECONOMIC GROWTH IN THE LARGE AND SMALL-SCALE ECONOMIES AND THE ROLE OF RESOURCES IN CONVERSION OF ENERGY-ORIENTED TO INNOVATION-DRIVEN ECONOMY - Kuznetsova, Natalia (Ekonomika, 2009)
The article deals with the economic growth in different scale economies, namely, resource-abundant and resource–driven countries and chances for the conversion of the latter into the knowledge-based mode of development. The paper deals with two problems 1) economic growth in different groups of the small-scale countries of the world economy through the estimate of the historical context ; 2) dynamics of the assessment in small and large transit economies.The goal of the article is to promote the idea of the resource-rich economies which find themselves at different stages of overcoming transitivity from the curse to the blessing type of economic growth. The hypothesis of the article is that sustainable economic development and continuous economic growth in transit economies could be achieved by means of the formation of the rent capitalism model in the large resource-rich countries. The methods used in the article are analysissynthesis, historical and logical methods of investigation, methods of international comparisons. The main conclusion of the article is that due to the formation of rent capitalism model growing gigantic countries play a predominant role in the world economy and in the global financial markets gaining the role of the savior during the expansion of the global financial crisis.